Structural stability of steel : concepts and applications for structural engineers - Galambos, T. V. (John Wiley & Sons, 2008)
This work on structural stability has been written primarily as a textbook to provide a clear understanding of theoretical stability behaviour. It will give readers a basic understanding of the design specifications developed by, for example, AISC, and implemented in building codes by IBC.
Keywords: Building, Iron and steel.; Structural stability.; elektronické knihy; electronic books